Analysis of ethnic influence on stillbirths and infant mortality in Bradford 1975-81. Issue 3 (September 1984) - Gillies, D R; Lealman, G T; Lumb, K M; Congdon, P
Abstract : The patterns of mortality from birth to 1 year in Bradford were studied in the seven year period 1975-81. Large differences in mortality between the Asian and non-Asian population were shown. In 1981 77% of Bradford Asian families were of Pakistani origin, the remaining 23% consisting of families from other parts of the Indian subcontinent and a few from East Africa. There were excess mortality with associated congenital abnormality in the Asian population. From 1975 to 1981 there were 133 deaths associated with congenital abnormality (a rate of 12.4 per 1000 total births) in the Asian population compared with a figure of 129 (4.8 per 1000) in the non-Asian population. The differences between the two groups are shown to be largely independent of social class, and other possible reasons for the discrepancy between the Asian and non-Asian populations are discussed.